Market quality analysis for electroplating services in metal finishing industries [microfilm] - Saravanan, Vigneswaran (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Mechanical Engineering (Materials)) - Universiti Teknologi Malaysia, 1999